Research on optimization of energy storage regulation model considering wind–solar and multi-energy complementary intermittent energy interconnection - Zhibin Liu; Boqian Liu; Xiaoyin Ding; Fei Wang (Energy Reports, 2022)
Wind and solar multi-energy complementation has become a key technology area in smart city energy system, but its inherent intermittency and random fluctuations have caused many negative effects on the stable operation of multi-energy system. Energy storage system has become a key link to solve the problem of stabilization and consumption of intermittent new energy in smart city. Based on the energy value tag and the optimization of equipment sequence, a comprehensive regulation model of wind–solar energy storage in smart city is established by using the spectrum analysis method. The output power curve of the system is divided into different frequency to optimize the energy storage configuration. And the appropriate equipment is selected in a specific scene of a smart park to verify, it shows the effectiveness of the model. Compared with the hierarchical multi-level control model, it can effectively suppress the long-term fluctuations of new energy sources such as wind and solar. It reduces the impact of peak–valley difference on the stability of grid operation and promotes the consumption of new energy. It selects the energy supply equipment of the system based on the energy value label and orders to participate in the scheduling, which can better meet the control needs of optimization goals in different control scenarios. According to energy demand, the park is divided into plot A and plot B. Plot A is dominated by high-tech office buildings and large shopping malls. Plot B is mostly residential quarters. It is calculated by Matlab calling the Cplex software, the economic cost of optimal dispatch in plot A is 3892.37 yuan, while the economic cost of optimal dispatch in plot B is 4316.75 yuan. The problem of integrated regulation of smart city energy is solved by the Cplex software, which uses the Matlab to read the excel file to get the basic matrix. Substituting the MOP (Multi-Objective Planning, MOP) model in the Cplex software into the matrix and adopting a hierarchical and multi-level control method has reduced the daily operating cost of the energy system by 15.91%. The results show that the hierarchical and multi-level regulation model has a certain positive effect on the level of new energy consumption in the smart city energy system. It also verifies the correctness and effectiveness of the comprehensive regulation model.